POTENSI TIGA GENUS BAKTERI DARI TIGA RIZOSFER TANAMAN SEBAGAI AGENSIA PENGENDALI HAYATI PENYAKIT LINCAT - Heru Adi Djatmiko; Triwidodo Arwiyanto; Bambang Hadisutrisno; Bambang Hendro Sunarminto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
Objectives of this research were to characterize three genera of bacteria isolated from three of crop rhizosphere, and to measure the ability of the antagonistic bacteria in suppressing lincat disease caused by Ralstonia solanacearum and Meloidogyne incognita. The research showed that the sixth bacteria were able to utilize some carbon and nitrogen compounds, degrade macromolecules, grew at different temperatures and salt contents, and grew at medium with chitin and pectin.  The bacteria isolated from pepper rhizosphere (Pf51, Ba4, Ba22), groundnut (Pf83), and eggplant (S4 dan S7) was included to fluorescent pseudomonads (Pf51 and Pf 83), Bacillus spp. (Ba4 and Ba22), and Streptomyces spp. (S4 and S7).  The sixth bacteria having the ability in antagonist.  The bacteria isolate having the best ability in suppressing Ralstonia solanacearum and Meloidogyne incognita was Streptomyces spp. (S4). The bacteria isolate having the best ability in suppresssing R. solanacearum by antibiosis and the inhibition mechanism by bacteriostatic was S4